Dissecting the signaling mechanisms of IL-7-mediated autophagy regulation in T-cell acute lymphoblastic leukemia - Lopes, Maria Inês Felizardo (2016)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2014